2018
DOI: 10.12669/pjms.345.15330
|View full text |Cite
|
Sign up to set email alerts
|

Post hysteroscopic progesterone hormone therapy in the treatment of endometrial polyps

Abstract: Objective:To find out the clinical effects of post hysteroscopic progesterone hormone therapy in the treatment of endometrial polyps in terms of clinical outcome and the expression of endometrial Vascular Endothelial Growth Factor (VEGF).Methods:Ninety-eight patients who were confirmed as endometrial polyp in the hospital from April 2014 and December 2016 were selected and divided into treatment group and a control group using random number table, 49 in each group. Patients in both groups were given hysterosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In this study, the overall recurrence rate of EPs in premenopausal women was 14.2% at 12 months after hysteroscopic polypectomy, which is consistent with rates reported in previous studies [14,[20][21][22]. Although, after subgroup analysis according to CE, the recurrence rate of EPs in premenopausal women increased to 26.6%, and CE played a harmful role in the recurrence of EPs.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the overall recurrence rate of EPs in premenopausal women was 14.2% at 12 months after hysteroscopic polypectomy, which is consistent with rates reported in previous studies [14,[20][21][22]. Although, after subgroup analysis according to CE, the recurrence rate of EPs in premenopausal women increased to 26.6%, and CE played a harmful role in the recurrence of EPs.…”
Section: Discussionsupporting
confidence: 91%
“…Post hysteroscopic progesterone hormone therapy was reported to have encouraging clinical effects in the treatment of endometrial polyps as it is shown to have effectively prevented the recurrence of endometrial polyps, and both a reduction of haemoglobin levels and endometrial thickness. 93 Progesterone appeared to be a valid therapeutic alternative for the management of endometrial polyps. 94…”
Section: Treatmentmentioning
confidence: 99%
“…Paradisi et al found that recurrence after endometrial hysteroscopic polypectomy was related to non-atypical concurrent hyperplasia and had nothing to do with appearance, age, parity, weight, or other demographic characteristics (17). The use of progesterone after endometrial polypectomy could significantly reduce the recurrence rate of polyps, which has been confirmed in some previous studies (18,19). After identifying the independent risk factors of endometrial polyp recurrence, we constructed a nomogram for predicting polyp recurrence using logistic regression analysis and verified the calibration curve.…”
Section: Discussionmentioning
confidence: 81%